Oral health status in 12 and 15-year-old schoolchildren - Milanović Milena; Bogdanović Nikolina; Jakšić Milica; Miličić-Lazić Minja (Serbian Medical Society - Dental Section, Belgrade, 2021)
Introduction: Dental caries is, along with periodontitis, the most frequent oral disease and represents a chronic, progressive, multifactorial process that leads to loss of hard dental tissues. The oral health status analysis and caries risk factors assessment in early childhood and adolescence are necessary for creating strategies in oral health promotion and preventive treatment. The aim of the present study was to evaluate caries prevalence in 12 and 15-year-old schoolchildren in Čukarica, a municipality of Belgrade. Material and method: The retrospective study included 409 schoolchildren of both genders. The oral health status was registered using the Klein-Palmer DMFT system (D - Decayed, M-Missing, F-Filled teeth). The methods of descriptive statistics were performed and p-values lower than 0.05 were considered statistically significant. Results The younger group included 214 children (52.3%) and the older group 195 (47.7%). Individual caries rate was higher in 15-year-old children (81.02%) comparing to 12-year-old (57%). The mean value of decayed teeth for all participants was 2.43 and of total DMFT was 8.99%. Conclusions: Oral health promotion programs gave positive results. Moreover, it is important to implement them in the underdeveloped regions of Serbia with an improvement of the oral health literacy of parents and raising awareness of oral diseases.